Pembentukan Kepribadian Muslim dalam Perspektif Filsafat Pendidikan Islam - Harahap, Radinal Mukhtar (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2017)
Management of forming muslim behavior according to Islamic education studies is accrued; first, concept , that educations should looked forward to the second Human Values, physically or non, body, soul, desire, hearth and mind. Second, from side of environment education should being conducted by all part around students, either, societies, state or its institution. Third, implementing, that implementing education of faith, education of science, educations of practice, education of moral and social education. forth, education should being strongly conducted to make the peoples felt closely to the Quran and remembering syahadah that the peoples promised to their God before, through knowledge and culture, learning, education, and ta’dib (morality)